Holographic imaging of cylindrical ultrasonic waves - Grulkowski, L.; Jankowski, D.; Kwiek, P. (Archives of Acoustics, 2006)
This report is devoted to the visualisation of standing cylindrical ultrasonic wave, generatedby a radially vibrating piezoelectric shell, by means of time-average holographic interferometry.The theoretical basis of this technique was introduced, and the expression of lightintensity distribution during holographic reconstruction of cylindrical waves was presented.Finally, the theory was verified by experimental findings. Quite a good agreement betweentheoretical predictions and experimental results was found.